2020
DOI: 10.1016/j.ijhydene.2019.03.071
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of volumetric hydrogen storage capacities of nanoporous carbons: Effect of dispersion interactions as a function of pressure, temperature and pore width

Abstract: Simulations of the hydrogen storage capacities of activated carbons require an accurate treatment of the interaction of a hydrogen molecule physisorbed on the graphitic-like surfaces of nanoporous carbons, which is dominated by the dispersion interactions. These interactions are described accurately by high level quantum chemistry methods such as the Coupled cluster method with single and double excitations and a non-iterative correction for triple excitations (CCSD(T)), but those methods are computationally v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…Regarding the way we use to simulate the local environment of a porous material based on BC 3 , it is important to remark that the pioneering experiments by Franklin [63] and the results of more recent experimental studies on nanoporous carbons [64,65] showed that these materials are mainly composed by slit-shaped pores, with a pore width distribution in the range of several to hundred angstroms. Previous calculations for graphene slit pores (i.e., two parallel graphene sheets separated by a distance in the range of nanometers) confirm that the local environment of porous carbon materials is well captured by means of such slit pores [21,60,61]. In the present work, slit pores made of two parallel BC 3 sheets in their most stable honeycomb configuration are used in the simulations.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…Regarding the way we use to simulate the local environment of a porous material based on BC 3 , it is important to remark that the pioneering experiments by Franklin [63] and the results of more recent experimental studies on nanoporous carbons [64,65] showed that these materials are mainly composed by slit-shaped pores, with a pore width distribution in the range of several to hundred angstroms. Previous calculations for graphene slit pores (i.e., two parallel graphene sheets separated by a distance in the range of nanometers) confirm that the local environment of porous carbon materials is well captured by means of such slit pores [21,60,61]. In the present work, slit pores made of two parallel BC 3 sheets in their most stable honeycomb configuration are used in the simulations.…”
Section: Introductionmentioning
confidence: 60%
“…The aim of the work presented here is to provide realistic predictions for the volumetric and gravimetric hydrogen storage capacities of a porous material containing Li-decorated BC 3 slit pores. To incorporate finite temperature and pressure, we combine results obtained from DFT calculations with those inferred from a quantum-thermodynamic model [21,[59][60][61][62]. A similar methodology has been used recently by us to investigate the hydrogen storage capacity of Li-decorated borophene slit pores, which were found to be optimal for hydrogen storage at low temperature [59].…”
Section: Introductionmentioning
confidence: 99%
“…Graphene slit pores were studied in Ref. [44] using the optB88-vdW functional, with the aforementioned approximation for the interaction potential of H 2 with graphene. The volumetric capacities, v c , of graphene slit pores published in Ref.…”
Section: Geometry Of the Slit Pores Formed By Two Parallel Li-decorated Borophene Sheetsmentioning
confidence: 99%
“…The volumetric capacities, v c , of graphene slit pores published in Ref. [44] will be plotted in this work, for comparative purposes. Other results presented here for graphene slit pores (the gravimetric capacities, g c , and the interaction potentials) are entirely new, although related with the results reported in that reference.…”
Section: Geometry Of the Slit Pores Formed By Two Parallel Li-decorated Borophene Sheetsmentioning
confidence: 99%
See 1 more Smart Citation